Antiprotozoal agents – Integration of drug discovery, medicinal chemistry, and advanced computational approaches: An in-depth review - Aviral Kaushik; Naureenbanu Makarani; Krupanshi Bharadava; Jeetaram Gehlot; Bhukya Vishnu Naik; Ankita Singh; Sumit Govil; Radhey Shyam Kaushal (The Microbe)
Protozoal diseases have been a global burden for decades, including fatal diseases that can lead to death, particularly in low- and middle-income countries. Many of these diseases are classified under Neglected Tropical Diseases (NTDs). Diseases such as malaria (Plasmodium spp.), Chagas disease (Trypanosoma cruzi), leishmaniasis (Leishmania spp.), primary amoebic meningoencephalitis (Naegleria fowleri), and trichomoniasis (Trichomonas vaginalis) continue to cause substantial morbidity and mortality. This review aims to address the growing urgency of protozoal drug resistance by consolidating current knowledge and highlighting recent advancements in treatment strategies. It responds to the rapid emergence of resistant strains and expanding gap between therapeutic needs and available options, emphasizing the importance of innovative, effective and sustainable approaches to antiprotozoal drug development.Although treatment options exist, the efficacy of many frontline and second-line drugs such as Amphotericin B and miltefosine has declined due to the widespread emergence of drug resistance. It has now become critical to explore the current state of drug resistance in these protozoal infections and to discuss recent advancements in drug discovery and therapeutic strategies. This review highlights both traditional and modern approaches, including repurposing, screening, combination therapies and computational tools like in silico modelling. These methods offer promising avenues for identifying novel compounds and overcoming resistance mechanisms. Despite advances in individual domains, such as target identification or molecular docking, major challenges persist. Challenges include limited healthcare access in endemic areas, inadequate NTD funding, adaptive pathogen evolution and an underdeveloped antiprotozoal drug pipeline. This review underscores the urgent need for interdisciplinary research and innovative therapeutic interventions to outpace resistance and improve global health outcomes. This integration that bridges medicinal chemistry with in silico design can serve as a valuable reference for cross-disciplinary collaboration. Addressing these gaps is essential for developing sustainable, effective treatments for protozoal diseases in the post-resistance era.